Aging and ABO blood type influence von Willebrand factor and factor VIII levels through interrelated mechanisms. (27th April 2016) - Albánez, S.; Ogiwara, K.; Michels, A.; Hopman, W.; Grabell, J.; James, P.; Lillicrap, D.
Abstract : Essentials von Willebrand factor (VWF) and factor VIII (FVIII) levels are modulated by age and ABO status. The effect of aging and ABO blood type on VWF and FVIII was assessed in 207 normal individuals. Aging and ABO blood type showed combined and bidirectional influences on VWF and FVIII levels. Aging and ABO blood type influence VWF levels through both secretion and clearance mechanisms. Summary: Background: The effect of aging and ABO blood type on plasma levels of von Willebrand factor (VWF) and factor VIII (FVIII) have been widely reported; however, a comprehensive analysis of their combined effect has not been performed and the mechanisms responsible for the age‐related changes have not been determined. Objectives: To assess the influence of aging and ABO blood type on VWF and FVIII levels, and to evaluate the contribution of VWF secretion and clearance to the age‐related changes. Methods: A cross‐sectional observational study was performed in a cohort of 207 normal individuals, whose levels of VWF, FVIII, VWF propeptide (VWFpp), VWFpp/VWF:Ag ratio and blood type A antigen content on VWF (A‐VWF) were quantified. Results: Aging and ABO blood type exerted interrelated effects on VWF and FVIII plasma levels, because the age‐related increase in both proteins was significantly higher in type non‐O individuals ( β = 0.011 vs. 0.005). This increase with age in non‐O subjects drove the differences between blood types in VWF levels, as the mean difference increased from 0.13 U/mL in the young to 0.57 U/mL in the old. Moreover, A‐VWF was associated with both VWF antigen ( β = 0.29; 95% confidence interval [CI], 0.09, 0.50) and VWF clearance ( β = −0.15; 95% CI, −0.25, −0.06). We also documented an effect of ABO blood type on VWF secretion with aging, as old individuals with blood type non‐O showed higher levels of VWFpp (mean difference 0.29 U/mL). Conclusions: Aging and ABO blood type have an interrelated effect on VWF and FVIII levels, where the effect of one is significantly influenced by the presence of the other.